Factors associated with breastfeeding in children aged 6 to 23 months - Souza, Thais Fernanda Sehnen de; Rauber, Larissa Naiana; Melhem, Angelica Rocha de Freitas; Vieira, Daniele Gonçalves; Silva, Catiusce Cabreira da; Saldan, Paula Chuproski (ABCS Health Sciences, 2020)
Introduction: The period between gestation and 24 months of age corresponds to the moment of opportunities for the development and growth of the child. Objective: To analyze factors associated with breastfeeding in children aged 6 to 23 months. Methods: Cross-sectional study carried out during the National Polio Vaccination Campaign 2012 in Guarapuava, Paraná Brazil with children aged 6-23 months, comprising a sample of 1,750 individuals. For the identification of the factors associated with breastfeeding, Poisson regression models were applied, estimating Prevalence Ratios (PR) and 95% Confidence Intervals (95% CI). Bivariate models were developed covering each of the independent variables and the dependent variable. Results: The independent factors associated with early breastfeeding interruption in 1,355 infants were: use of baby-bottle (PR 4.74, CI 3.45-6.52), use of pacifier (PR 1.47, CI 1.30-1.66), not being breastfed in the first hour of life (PR 1.14, CI 1.05-1.25) and mother working out of home (PR 1.12, CI 1.01-1.24). Maternal schooling lower than 8 years was a protective factor for the continuity of breastfeeding (PR 0.88, CI 0.80-0.96). Conclusions: The use of nipples, not being breastfed in the first hour of life and maternal work interfered in the continuity of breastfeeding. From this knowledge it is possible to propose recommendations for actions to promote breastfeeding at the local level.